On the Reactivity of Phosphaalumenes towards C−C Multiple Bonds. Issue 10 (25th January 2023) - Nees, Samuel; Wellnitz, Tim; Dankert, Fabian; Härterich, Marcel; Dotzauer, Simon; Feldt, Milica; Braunschweig, Holger; Hering‐Junghans, Christian
Abstract: Heterocycles containing group 13 and 15 elements such as borazines are an integral part of organic, biomedical and materials chemistry. Surprisingly, heterocycles containing P and Al are rare. We have now utilized phosphaalumenes in reactions with alkynes, alkenes and conjugated double bond systems. With sterically demanding alkynes 1, 2‐phosphaalumetes were afforded, whereas the reaction with HCCH or HCCSiMe3 gave 1, 4‐phosphaaluminabarrelenes. Using styrene saturated 1, 2‐phosphaalumates were formed, which reacted further with additional styrene to give different regio‐isomers of 1, 4‐aluminaphosphorinanes. Using ethylene, a 1, 4‐aluminaphosphorinane is obtained, while with 1, 3‐butadiene a bicyclic system containing an aluminacyclopentane and a phosphirane unit was synthesized. The experimental work is supported by theoretical studies to shed light on the mechanism governing the formation of these heterocycles. Abstract : Phosphaalumenes react with alkynes and alkenes. Depending on the steric profile of the alkyne either 1, 2‐phosphaalumetes in a formal [2 2] cycloaddition or zwitterionic 1, 4‐phosphaaluminabarrelenes through threefold insertion into the Al−P bond are obtained. With alkenes 1, 2‐phosphalumates and 1, 4‐aluminaphosphorinanes are obtained. Computational studies corroborate the contrasting pathways and underline the role of the aluminum center.